The formation of early career primary school teachers’ professional subjectivity in Greece and England - Selechopoulou, Vasiliki-Eleni (2024)
This study investigates how complex relations between discourses, governmentalities, power practices, and early-career primary school teachers’ freedom shape their professional subjectivities, examining the countries of Greece and England. Focusing on the period between 2019 and 2021, it seeks to illustrate the games of power and truth that shape teachers’ ways of being and acting. Education reforms introduced in both countries during that period indicate that early-career teachers' processes of becoming are a central area of focus in education policy. However, the review of the literature suggests that the formation of teachers’ professional subjectivities is still understudied. Thus, in this context, this comparative study draws from ethnographic and critical traditions and combines different research instruments to elucidate this complex phenomenon. This study mobilizes a post-structuralist approach to the formation of professional subjectivity, combining a Foucauldian theory of the subject with the analysis of policy documents, in-depth interviews and unstructured observations. This combination of methods offers nuanced insight into how discourses of the profession, governmentalities, power practices and teachers' freedom intersect to shape the way teachers form professional subjectivities in Greece and England. The findings of this study map out the processes that shape early-career teachers’ professional subjectivities in Greece and England. They present these processes as dynamic, historically situated and interlinked with the characteristics of each education system and the prevailing political rationalities. The study illustrates that early-career teachers’ professional subjectivities are shaped in relation to the policy discourses that indicate what is desirable and valued in each context, as well as the practices and relations of power and freedom that externally and internally shape the educators’ possibilities of becoming. Additionally, participants’ experiences indicate that the teachers maintain an active role in these processes by tactically navigating and (re)forming their professional selves. This study adds to the literature by constituting a body of knowledge that maps out the processes that form early-career teachers’ professional subjectivities from a post-structural comparative stance. Adopting a comparative Foucauldian perspective, it argues that multiple possibilities of acting and becoming are open to early-career teachers depending on their historical contexts. By giving an insight into the breadth of these possibilities, it encourages the unsettling of normalised practices that attach teachers to particular modes of being.